DEVELOPING ENGLISH READING MATERIALS FOR STUDENTS OF CERDAS MURNI ISLAMIC JUNIOR HIGH SCHOOL - Diah Ayu Nanda and Morada Tetty (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2016)
This study aimed to develop English reading materials needed for students ofCerdas Murni Islamic Junior High School through Authentic Material Approach(AMA).The objective of this study was to develop relevant English readingmaterials to the needs of Cerdas Murni Islamic Junior High School studentsespecially eight grade . This study was conducted by Research and Development(R&D) design through six phases: 1) Collecting data, 2) Analyzing data, 3)Developing new materials, 4) Validating product 5) Revising materials, 6) finalproduct. The data of this research were from the existing materials, syllabus,students’ questionnaire, and the teachers’ interview. The result of this researchshowed that the existing materials were not suitable to the Islamic schoolstudents’ needs.. Therefore, new English reading materials were developedthrough Authentic Material Approach (AMA) principles in order to meet theIslamic students’ needs. Furthermore, developing English reading materials wererecount text. Recount text expose personal recount “Tarawih Changed his Lifeand the biographical recounts of Prophet Muhammad SAW and Shalahuddin Al-Ayyubi”. The English reading materials were validated by English teacher andEnglish lecturer. Both of them agreed that new English reading materials weresuitable with the Islamic school students’ needs.